2020
DOI: 10.3390/coatings10111079
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Dislocation Plasticity Mechanism of Nanoscale Ductile Materials in the Cold Gas Dynamic Spray Process

Abstract: The dislocation plasticity of ductile materials in a dynamic process of cold gas spraying is a relatively new research topic. This paper offers an insight into the microstructure and dislocation mechanism of the coating using simulations of molecular dynamics (MD) because of the short MD simulation time scales. The nano-scale deposition of ductile materials onto a deformable copper substrate has been investigated in accordance with the material combination and impact velocities in the particle/substrate interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Therefore, simulations based on molecular dynamics (MD) can be considered to analyze the bonding at the interface. MD simulations have reported the effect of impact velocity on interfacial behavior of Ti and Ni particles on Ti substrates, that have been experimentally validated [130,[138][139][140].…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 88%
“…Therefore, simulations based on molecular dynamics (MD) can be considered to analyze the bonding at the interface. MD simulations have reported the effect of impact velocity on interfacial behavior of Ti and Ni particles on Ti substrates, that have been experimentally validated [130,[138][139][140].…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 88%
“…In this Special Issue, not only the potential use of the 3D technique for coating is covered, but the basic mechanisms of coating formation are also included. Oyinbo et al [3] studied the basic mechanism of layer formation in the CS technique using molecular dynamics while considering ductile materials as examples. They showed that due to the jetting phenomena at the particle/substrate interface, materials deform.…”
mentioning
confidence: 99%